ORGANIZATIONAL CAPABILITIES, STRATEGIC MANAGEMENT ACCOUNTING AND FIRM PERFORMANCE - Lay, Tan Ah; Jusoh, Ruzita (Jurnal Akuntansi dan Keuangan Indonesia, 2017)
From a resource-based view perspective, the paper provides empirical evidence on new emerging strategic management accounting (SMA), its association with organizational capabilities (market orientation, entrepreneurship, innovativeness and organizational learning) and the interlinkages among these four elements of organizational capabilities. Partial least squares (PLS) technique was used to test the contingency model. Using the mail survey data of 103 manufacturing strategic business units (SBUs) of public listed companies in Malaysia, the results found that the four organizational capabilities - market orientation, entrepreneurship, innovativeness and organizational learning - collectively give rise to positional advantage leading to enhanced firm performance. SMA techniques are found to support the internal organizational capabilities. However, SMA usage is not associated with firm performance, indicating that the mediation role of SMA usage on the relationship between organizational capabilities and firm performance is not supported. The results confirm that a firm can attain above average performance if it possesses and emphasizes the four organizational capabilities collectively and these four organizational capabilities collectively are also important to support the usage of SMA techniques which can provide useful information for improvement of internal capabilities as well as resource allocation and utilization.